Acute Toxicity And Behavioural Responses Of Heteropneustes Fossilis To An Organophosphate Insecticide, Dimethoate - ANOOP KUMAR SRIVASTAVA; DIWAKAR MISHRA; SHILPEE SHRIVASTAVA; SUNIL KUMAR SRIVASTAV; AJAI K. SRIVASTAV (International Journal of Pharma and Bio Sciences, 2010)
Static renewal evaluation of the acute toxicity of an organophosphate pesticide, dimethoate against the freshwater fish H. fossilis was conducted in the laboratory. H. fossilis showed behavioural changes against dimethoate intoxication. There were increased opercular movement, sluggish, lethargic and abnormal swimming, loss of buoyancy and muscular tetany. The treated fishes also showed fading of their body colour. The LC50 values of dimethoate to the freshwater catfish, Heteropneustes fossilis at various exposure periods are 15.92 mg/l for 24 h; 13.42 mg/l for 48 h; 12.39 mg/l for 72 h and 11.34 mg/l for 96 h. The upper confidence limits were 16.59, 14.72, 13.54 and 12.86 mg/l for 24, 48, 72 and 96 h and lower confidence limits were 15.32, 12.18, 11.23 and 9.79 mg/l, respectively. From the present study it seems that the freshwater catfish, H. fossilis is more susceptible to dimethoate toxicity as the LC50 value for this organophosphate is less than other reported fish species. These results indicate that dimethoate exposure to the fish caused toxic effects.